Intrauterine growth restriction results in persistent vascular mismatch in adulthood. (21st November 2017) - Kuo, Anderson H.; Li, Cun; Huber, Hillary F.; Clarke, Geoffrey D.; Nathanielsz, Peter W.
Abstract : Key points: Intrauterine growth restriction (IUGR) increases offspring risk of chronic diseases later in life, including cardiovascular dysfunction. Our prior studies suggest biventricular cardiac dysfunction and vascular impairment in baboons who were IUGR at birth because of moderate maternal nutrient reduction. The current study reveals changes in artery sizes, distensibility, and blood flow pattern in young adult IUGR baboons, which may contribute to cardiac stress. The pattern of abnormality observed suggests that vascular redistribution seen with IUGR in fetal life may continue into adulthood. Abstract: Maternal nutrient reduction induces intrauterine growth restriction (IUGR), increasing risks of chronic diseases later in life, including cardiovascular dysfunction. Using ultrasound, we determined regional blood flow, blood vessel sizes, and distensibility in IUGR baboons (8 males, 8 females, 8.8 years, similar to 35 human years) and controls (12 males, 12 females, 9.5 years). The measured blood vessels were larger in size in the males compared to females before but not after normalization to body surface area. Smaller IUGR normalized blood vessel sizes were observed in the femoral and external iliac arteries but not the brachial or common carotid arteries and not correlated significantly with birth weight. Mild decrease in distensibility in the IUGR group was seen in the iliac but not the carotid arteries without between‐sex differences. In IUGR baboons there was increased carotid arterial blood flow velocity during late systole and diastole. Overall, our findings support the conclusion that region specific vascular and haemodynamic changes occur with IUGR, which may contribute to the occurrence of later life cardiac dysfunction. The pattern of alteration observed suggests vascular redistribution efforts in response to challenges in the perinatal period may persist into adulthood. Further studies are needed to determine the life course progression of these changes. Key points: Intrauterine growth restriction (IUGR) increases offspring risk of chronic diseases later in life, including cardiovascular dysfunction. Our prior studies suggest biventricular cardiac dysfunction and vascular impairment in baboons who were IUGR at birth because of moderate maternal nutrient reduction. The current study reveals changes in artery sizes, distensibility, and blood flow pattern in young adult IUGR baboons, which may contribute to cardiac stress. The pattern of abnormality observed suggests that vascular redistribution seen with IUGR in fetal life may continue into adulthood.